Adiabatic superconducting cells for ultra-low-power artificial neural networks - Schegolev, Andrey E.; Klenov, Nikolay V.; Soloviev, Igor I.; Tereshonok, Maxim V. (Beilstein Journal of Nanotechnology, 2016)
We propose the concept of using superconducting quantum interferometers for the implementation of neural network algorithms with extremely low power dissipation. These adiabatic elements are Josephson cells with sigmoid- and Gaussian-like activation functions. We optimize their parameters for application in three-layer perceptron and radial basis function networks.
Keywords: adiabatic superconductor cells; artificial neural networks; energy efficiency; Josephson effect; superconductivity